2009
DOI: 10.1902/jop.2009.080316
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Outcome of Root‐Resection Therapy in Molars: A 10‐Year Retrospective Study

Abstract: Root resection to treat periodontal problems had a better prognosis than for non-periodontal problems. To achieve a good result, it was important that the remaining roots had >50% bone support. This guideline may help to improve the predictability of root-resection therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 27 publications
3
75
2
6
Order By: Relevance
“…Prognosis for root resected posterior teeth is good provided the fracture can be removed in its entity. The retention rate of root resected teeth at 10 years has been reported at 70.2% [8]. Some investigators have compared the prognosis of root resection therapy to that of implant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis for root resected posterior teeth is good provided the fracture can be removed in its entity. The retention rate of root resected teeth at 10 years has been reported at 70.2% [8]. Some investigators have compared the prognosis of root resection therapy to that of implant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of root resection has been welldocumented in previous studies [8,[17][18][19]. The 4-year survival rate of maxillary molars after root amputation is reported to be 93% [20] and long-term survival of teeth after root amputation ranges from 87% to 95% [15].…”
Section: Discussionmentioning
confidence: 99%
“…11 Park et al reported a success rate of 60.1% for root resection therapy at the end of a 10-year follow-up period. 12 The authors were also suggested that periodontal reasons were the most common causes for failure.…”
Section: Discussionmentioning
confidence: 99%